Do Municipal Climate Protection Activities interfere with Individual Engagement? - Martin Kesternich; Lara Bartels (ZBW - Leibniz Information Centre for Economics, 2021)
The Paris Agreement aims at limiting the global average temperature increase to well below 2êC above preindustrial levels. A key component of the agreement are "nationally determined contributions" (NDC). For this, non-state actors such as civil society groups, economic actors, and subnational and local actors (e.g. Municipalities) play a decisive role. However, a successful integration of non-state actors must happen within the larger framework of the global climate regime. Literature has already stressed the importance of a "polycentric" or multi-level climate governance as an enabler for a transformation climate governance. As the role of non-state actors for reaching the climate goals has received little attention within research, our research focuses on the lowest rungs of the multi-level climate governance ladder and analyses feedback loops between local non-state actors, here municipalities, and individual climate protection activities. With a framed-field experiment we aim to analyze the relationship between individual commitment to climate protection and the commitment of other fellow citizens, and the interaction between individual commitment and municipal engagement. Special attention is paid on potential crowding in or crowding-out effects. Our first preliminary results indicate that the share of contributors and the mean contributions are the highest in the citizen-reference treatment. The city-treatment values are compared to the citizentreatment reference both at the extensive and intensive margin significantly lower. Additionally, we find that stated personal traits and attitudes predict pro-environmental behavior in form of the contribution very well.
Keywords: Q51; Q54; C93; H41; 330; voluntary provision of environmental public goods; voluntary climate change mitigation; carbon sequestration; willingness to pay; co-benefits